COMPARATIVE STUDY OF CONSUMER BUYING BEHAVIOR AT MUSIC PLAYING AND NON MUSIC PLAYING SHOE STORES - Menajang, Irene Ladies (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2014)
Consumers are not only shopping to meet their needs, but they also are going to look for stores that provide a pleasant experience. Music can be an important compnent of store atmosphere and plays a role in purchase decision meaking process. Background music can be heard in almost all fashion stores including shoe stores in Manado. But, there are still shoe stores that are not playing background music. The objective of this research is to analyze the significant difference of consumer buying behavior at music playing and non music playing shoe stores. The type of this research is a comparative study. This research use quantitative method and independent sample t-test to analyze the data. The population observed are people in Manado who has experience in music playing and non music playing shoe stores in Manado which are Payless and Everbest shoe stores. The samples of this research are 100 respondents, consist of 50 respondents that have experience in music playing store and 50 respondents that have experience in non-music playing store, which are Payless and Everbest. This study reveals that there is no significant difference in consumer buying behavior at music playing and non music playing shoe stores. Music can be an important element in store environment, but music has no influence to motivate consumers to frequently visit and reccomend the store to the others. Â  Keywords: consumer buying behavior, music